Sahel Rainfall Projections Constrained by Past Sensitivity to Global Warming. Issue 18 (20th September 2022) - Schewe, Jacob; Levermann, Anders
Abstract: Africa's central Sahel region has experienced prolonged drought conditions in the past, while rainfall has recovered more recently. Global climate models project anything from no change to a strong wetting trend under unabated climate change; and they have difficulty reproducing the complex historical record. Here we show that when a period of dominant aerosol forcing is excluded, a consistent wetting response to greenhouse‐gas induced warming emerges in observed rainfall. Using the observed response coefficient estimate as a constraint, we find that Coupled Model Intercomparison Project Phase 6 climate models with a realistic past rainfall response show a smaller spread, and higher median, of projected future rainfall change, compared to the full ensemble. In particular, very small or negative rainfall trends are absent from the constrained ensemble. Our results provide further evidence for a robust Sahel rainfall increase in response to greenhouse‐gas forcing, consistent with recent observations, and including the possibility of a very strong increase. Plain Language Summary: Rainfall is a critical resource for a large population in the African Sahel region, but rainfall levels have strongly varied in the past. It is unclear what will happen in the next decades, because some climate models suggest little to no change in average rainfall, while other models project a strong increase due to climate change. Our study aims to narrow down this uncertainty. In the past, both greenhouse gases and aerosols influenced Sahel rainfall, to different degrees during different periods; and models may not capture both mechanisms equally well. However, future rainfall changes will likely be driven mainly by greenhouse gas levels. We identify models that closely match the rainfall change that was observed in a recent period with dominant greenhouse gas forcing. These models also tend to project stronger rainfall increases than other models. Indeed, their multi‐model mean projection is an increase by almost 50% by 2040; while none of them projects stable rainfall levels or even a reduction. Thus, it appears more likely now that rainfall in the Sahel will increase substantially over the next few decades. Key Points: We identify the response of Sahel rainfall to greenhouse gas‐induced global warming in the historical record Many global climate models of the latest generation (Coupled Model Intercomparison Project Phase 6) do not reproduce the observed rainfall response Observational constraint reduces model spread and implies stronger rainfall increase under further warming than in full ensemble